Antibacterial Activity of Citronella Essential Oil from Cymbopogon nardus (L.) Rendle) Against Methicillin-Resistant Staphylococcus aureus - Sari, Irma; Misrahanum, Misrahanum; Faradilla, Meutia; Ayuningsih, Cut Mutia; Hilda Maysarah (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Irrational antibiotic use in the treatment of infectious diseases can result in the emergence of antibiotic-resistant bacterial strains, such as Methicillin Resistant Staphylococcus aureus (MRSA). The purpose of this study is to determine the physical properties of citronella essential oil (Cymbopogon nardus (L.) Rendle) and to assess its antibacterial activity against MRSA. Citronella essential oil was extracted using a water-steam distillation method, yielding 0.5 percent. Citronella essential oil has a specific gravity of 0.904, a refractive index of 1.470, and is slightly soluble in 80 percent ethanol. All of these parameters were in accordance with the Indonesian Standard Requirement (SNI) for Citronella essential oil. The disc diffusion assay was used to test the antibacterial activity of this Citronella essential oil. The result indicated that Citronella essential oil has an activity to inhibit MRSA invitro.